2013
DOI: 10.1007/s12640-013-9433-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Curcumin Against Rotenone and Salsolinol-Induced Toxicity: Implications for Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a debilitating neurodegenerative disorder that results from the loss of or damage to dopaminergic cells in the substantia nigra. Exposure to either the pesticide rotenone or the endogenous neurotoxin salsolinol has been shown to mimic this dopaminergic cell loss. In this study we first sought to determine whether combination of rotenone and salsolinol would result in an additive or synergistic toxicity. For this purpose we utilized SH-SY5Y cells, a human neuroblastoma cell line that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 47 publications
3
36
1
1
Order By: Relevance
“…Recent studies have suggested that the flavonoids exhibit protection against neurodegeneration [19,20]. Naringin, a well-known flavanone glycoside of grape fruits, e.g., Citrus paradise, Citrus unshiu, and Citrus sinensis, has been reported to attenuate the oxidative stress, apoptosis, and inflammation, demonstrated to possess neuroprotective effect [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that the flavonoids exhibit protection against neurodegeneration [19,20]. Naringin, a well-known flavanone glycoside of grape fruits, e.g., Citrus paradise, Citrus unshiu, and Citrus sinensis, has been reported to attenuate the oxidative stress, apoptosis, and inflammation, demonstrated to possess neuroprotective effect [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin rescued α-synuclein-induced cell death (15). By targeting histone deacetylase (HDAC), curcumin promisingly prevented apoptosis and improved motor defi cits in Parkinson's disease (PD) in rat model (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Sal in the low concentrations (50 and 100 µM) activated as a neuroprotective factor; however, at its tenfold concentration (500 µM) it activated as a neurotoxic factor, which significantly enhanced the glutamate-induced neurotoxicity [25]. Similar data of Sal were observed in MTT assay [51]. The opposite effects of Sal suggest that its toxic role might be exerted along with its accumulation of mitochondrial damage after the vicious cycle we proposed occurs.…”
Section: The Major Neurotoxic Ctiqsmentioning
confidence: 58%